Two Undergraduate Students' Journal Reviewing Experiences - Susan Chan; Nuha Mohammed (Arizona State University, 2023)
This paper describes the benefits of student-run publications from the perspective of two undergraduate students. Based on their experiences, the commentary elaborates how reviewing for a student journal has contributed to their growth as writers and developed a sense of community.